Fidelity and costs of implementing the integrated chronic disease management model in South Africa - Lebina, Limakatso (Department of Public Health and Family Medicine, 2021)
Background: The health systems in many low-middle income countries are faced with an increasing number of patients with non-communicable diseases within a high prevalence of infectious diseases. Integrated chronic disease management programs have been recommended as one of the approaches to improve efficiency, quality of care and clinical outcomes at primary healthcare level. The South African Department of Health has implemented the Integrated Chronic Disease Management (ICDM) Model in Primary Health care (PHC) clinics since 2011. Some of the expected outcomes on implementing the ICDM model have not been achieved, and there is a dearth of studies assessing implementation outcomes of chronic care models, especially in low-middle income countries. This thesis aims to assess the degree of fidelity, moderating factors of fidelity and costs associated with the implementation of the ICDM model in South African PHC clinics. Methods: The study was a cross-sectional study design using mixed methods and following the process evaluation conceptual framework. A total of sixteen PHC clinics in the Dr. Kenneth Kaunda (DKK) health district of the North West Province as well as the West Rand (WR) health district of the Gauteng Province, that were ICDM pilot sites were included in the study. The degree of fidelity in the implementation of the ICDM model was evaluated using a fidelity criterion from the four major components of the ICDM model as follows: facility reorganization, clinical supportive management, assisted self-support and strengthening of the support systems. In addition, the implementation fidelity framework was utilized to guide the assessment of ICDM model fidelity moderating factors. The data on fidelity moderating factors were obtained by interviewing 30 purposively selected healthcare workers. The abbreviated Denison Organizational Culture (DOC) survey was administered to 90 healthcare workers to assess the impact of three cultural traits (involvement, consistency and adaptability) on fidelity. Cost data from the provider's perspective were collected in 2019. The costs of implementing the ICDM model current activities for three (facility reorganization, clinical supportive management and assisted self-management) components and additional costs of implementing with enhanced fidelity were estimated. Costs data was collected from budget reviews, interviews with management teams, and other published data. Descriptive statistics were used to describe participants and clinics. Fidelity scores were summarized using medians and proportions and compared by facilities and health districts. Qualitative data were analysed thematically. Pearson correlation coefficient was utilized to assess the association between fidelity and culture. The annual ICDM model implementation costs per PHC clinic and patient per visit were presented in 2019 US dollars. Results: The 16 PHC clinics had comparable patient caseload, and a median of 2430 (IQR: 1685-2942) patients older than 20 years received healthcare services in these clinics over six months. The overall implementation fidelity of the ICDM model median score was 79% (125/158, IQR: 117-132); WR was 80% (126/158, IQR: 123-132) while DKK was 74% (117/158, IQR: 106-130), p=0.1409. The highest clinic fidelity score was 86% (136/158), while the lowest was 66% (104/158). The fidelity scores for the four components of the ICDM model were very similar. A patient flow analysis indicated long (2-5 hours) waiting times and that acute and chronic care services were combined onto one stream. Interviews with healthcare workers revealed that the moderating factors of implementation fidelity of the ICDM model were the existence of facilitation strategies (training and clinical mentorship); intervention complexity (healthcare worker, time and space integration); and participant responsiveness (observing operational efficiencies, compliance of patients and staff attitudes). Participants also indicated that poor adherence to any one component of the ICDM model affected the implementation of the other components. Contextual factors that affected fidelity included supply chain management, infrastructure and adequate staff, and balanced patient caseloads. The overall mean score for the DOC was 3.63 (SD = 0.58), the involvement cultural trait had the highest (3.71; SD = 0.72) mean score, followed by adaptability (3.62; SD = 0.56), and consistency (3.56; SD = 0.63). Although there were no statistically significant differences in cultural scores between PHC clinics, culture scores for all three traits were significantly higher in WR (involvement 3.39 vs 3.84, p= 0.011; adaptability 3.40 vs 3.73, p= 0.007; consistency 3.34 vs 3.68, p= 0.034). The mean annual cost of implementing the ICDM model was $148 446.00 (SD: $65 125.00) per clinic, and 84% ($124 345.00) was for current costs while additional costs for higher fidelity accounted for were 16% ($24 102.00). The mean cost per patient per visit was $6.00 (SD:$0.77). Conclusion: There was some variability of fidelity scores on the components of the ICDM model by PHC clinics, and there are multiple (context, participant responsiveness, intervention complexity and facilitation strategies) interrelated moderating factors influencing implementation fidelity of the ICDM model. Organizational culture needs to be purposefully influenced to enhance adaptability and consistency cultural traits of clinics to enhance the ICDM model's principles of coordinated, integrated, patient-centred care. Small additional costs are required to implement the ICDM model with higher fidelity. Recommendations: Interventions to enhance the fidelity of chronic care models should be tailored to specific activities that have low degree of adherence to the guidelines. Addressing some of the moderating factors like training and mentoring of staff members, role clarification and supply chain management could contribute to enhanced fidelity. Organizational culture enhancements to ensure that the prevailing culture is aligned with the planned quality advancements is recommended prior to the implementation of new innovative interventions. Further research on the cost-effectiveness of the ICDM model in middle-income countries is recommended.